Extended X-ray absorption fine structure and X-ray diffraction studies of Mn-doped PZN-PZT ceramics - Ngamjarurojana A. (2014)
In this work, the selected compositions of a combination between perovskite piezoelectric ceramics lead zinc niobate (PZN) and lead zirconate titanate (PZT), close to the morphotropic phase boundary (MPB) i.e. the 0.2PZN-0.8PZT, doped with MnO2 concentrations of 0.0-0.9 wt% were fabricated by a simple solid-state reaction and a pressureless sintering techniques. X-ray diffraction (XRD) spectra from these materials reveal transformation of the tetragonal into the rhombohedral structure. The local structure of Mn was analyzed by mean of synchrotron extended X-ray absorption fine structure (EXAFS) measurements at the Mn K-edge. The correlation between the structural changes and the Mn content was analyzed and compared. The EXAFS analysis indicates that Mn ions should occupy the B-sites in PZN-PZT structure and plays a critical role for the hard ferroelectric behavior of the materials.